2008
DOI: 10.1159/000114538
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery for the Management of Orbital Diseases

Abstract: The indications for endoscopic sinus surgery (ESS) have been widely expanding since its introduction into sinus surgery. ESS has become an ideal method to manage certain orbital diseases and has the advantages of excellent visualization with minimal cosmetic and functional morbidity. In the Department of Otolaryngology of Taichung Veterans General Hospital from 1988 to 2005, 3,136 patients received ESS. Among them, a total of 108 patients received ESS for orbital diseases. These orbital diseases included orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Endoscopic sinus surgery has become an ideal method for treatment of certain orbital diseases and has the advantages of excellent visualization with minimal cosmetic and functional morbidity. 11 The indications for Endoscopic sinus surgery have been rapidly expanding since its introduction in nose and sinus surgery. Endoscopic sinus surgery is indicated any time when we observe acute sinusitis with complications.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic sinus surgery has become an ideal method for treatment of certain orbital diseases and has the advantages of excellent visualization with minimal cosmetic and functional morbidity. 11 The indications for Endoscopic sinus surgery have been rapidly expanding since its introduction in nose and sinus surgery. Endoscopic sinus surgery is indicated any time when we observe acute sinusitis with complications.…”
Section: Introductionmentioning
confidence: 99%
“…Within the review, sixteen of the included studies reported objective outcomes in the form of endoscopic findings. The endoscopic findings were either reported as part of validated scoring scales (1,7,(16)(17)(18)(19)21,22,(25)(26)(27)(28) or nonvalidated systems (15,20,23,24,30) . Seven studies reported endoscopic improvement (15,(17)(18)(19)(22)(23)(24) , whereas the remainder of the studies reported no benefit (endoscopic) from antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies specified within their inclusion criteria for participants to have recently undergone FESS prior to the study (17)(18)(19)(20)25) or as part of the study (15,22,23,26,30) . However, a number of studies specifically excluded participants whom had recent FESS prior (range 3 to 12 weeks) to the medical intervention (16,21,27,29) . The studies that excluded FESS prior to intervention argued that surgery would positively influence outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations